Research trends in critical thinking skills in mathematics: a bibliometric study - Arif Hidayatul Khusna; Tatag Yuli Eko Siswono; Pradnyo Wijayanti (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study systematically reviews and analyzes previous studies’ literature to identify the research gaps and the steps that must be taken for research on critical thinking in further mathematics education. Two methods, namely bibliometric analysis and descriptive content analysis, were used to achieve this goal. Data for the bibliometric analysis was obtained from the Scopus database, with the keywords “critical thinking” and “mathematics” Documents accessed are limited to the publication range of 2012-2022. The results show that the number of critical thinking research in mathematics has increased significantly, with a peak in 2021 of 65 articles; the United States has the most research and citations. The source that received the most citations was the journal Educational Studies in Mathematics. The evolution of the theme of critical thinking in mathematics began to link critical thinking with collaboration learning, mathematics education, teacher education, engineering, education, and collaborative learning. The quantitative approach with a student sample, tests as data collection instruments, and the analysis of variance (ANOVA) method is the methodology most often used by researchers. The results of this study are likely helpful for other researchers who will examine critical thinking skills in mathematics, namely as a research guide that they will develop. In addition, the existence of several research gaps can motivate other researchers to fill these gaps to contribute to improving the quality of critical thinking in mathematics.